Applications of Negotiation Theory to Water Issues - Carlo Carraro; Carmen Marchiori; Alessandra Sgobbi (Fondazione Eni Enrico Mattei (FEEM), 2005)
The purpose of the paper is to review the applications of non-cooperative bargaining theory to water related issues which fall in the category of formal models of negotiation. The ultimate aim is that to, on the one hand, identify the conditions under which agreements are likely to emerge, and their characteristics; and, on the other hand, to support policy makers in devising the rules of the game that could help obtain a desired result. Despite the fact that allocation of natural resources, especially of trans-boundary nature, has all the characteristics of a negotiation problem, there are not many applications of formal negotiation theory to the issue. Therefore, this paper first discusses the non-cooperative bargaining models applied to water allocation problems found in the literature. Particular attention will be given to those directly modelling the process of negotiation, although some attempts at finding strategies to maintain the efficient allocation solution will also be illustrated. In addition, this paper will focus on Negotiation Support Systems (NSS), developed to support the process of negotiation. This field of research is still relatively new, however, and NSS have not yet found much use in real life negotiation. The paper will conclude by highlighting the key remaining gaps in the literature.
Keywords: C72; C78; Q25; 330; Negotiation theory; Water; Agreeements; Stochasticity; Stakeholders; Verhandlungstheorie; Wasserversorgung